Servant Leadership and Spirituality Among Undergraduate and Graduate Nursing Students. - Maglione, Joyce L.; Neville, Kathleen (Journal of Religion & Health, 2021)
Nursing students represent the future of nursing. In today's increasingly complex health care environment nurse leaders must develop a distinct leadership style based on methodologically sound research to shape tomorrow's clinical practice. The purpose of this study is to determine the relationship between spirituality and servant leadership characteristics in undergraduate and graduate nursing students. Although the relationship between these two concepts has been studied in the workplace, less is known about the links of servant leadership and spirituality among nursing students. Data from 66 student participants were analyzed using the Servant Leadership and Spirituality Scales. The results indicated nursing students had relatively high levels of spirituality and servant leadership. A significant positive association was found between overall servant leadership and spirituality scores. Servant leadership characteristics increased from Bachelor of Science in Nursing (BSN) to Master of Science in Nursing (MSN) program students, but then decreased among the doctoral students. A decline in servant leadership was also demonstrated in nurses in practice greater than 10 years. Spirituality scores declined slightly in nurses' early years of practice, then rebounded and continued to progress with increased years of practice. The authors concluded that students that select nursing as a professional career may inherently possess characteristics of servant leadership and spirituality.